The Effectiveness of a Training Program Offered on the Electronic Digital Platform to Develop Digital Marketing Design Skills for Trainees of the Industrial Secondary Institute (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to investigate the effectiveness of a training program delivered on an electronic platform(coursera) to enhance digital marketing design skills among trainees at the Secondary Industrial In the city of Jeddah, in the Kingdom of Saudi Arabia. By applying action research on a purposefully selected experimental sample, the research sample included (20) second-year secondary school trainees from the computer science track at the Secondary Industrial Institute in Jeddah. A pre- and post-assessment test was developed specifically for the instructional design in this study.The research tool consisted of two main axes: the first axis focused on designing the digital marketing product, and the second axis on writing digital marketing content. The study results revealed statistically significant differences between the pre-test and post-test scores, favoring the post-test application across all skills represented by the scale. The study also recommended training small business owners affiliated with technical and vocational training and graduates of the Secondary Industrial Institute to develop digital marketing design skills in their marketing campaigns.
Keywords: E-learning; Technical and Vocational Training; Marketing; Professional Skills Development